Diatom Voucher Flora of Epilithic Habitats in the Mula-Mutha River Basin, Maharashtra, India, with Insights into Seasonal Indicator Taxa - Nayak, Pratyasha; Karthick, Balasubramanian (Phytotaxa, 2026)
Natural and anthropogenic changes can alter the surface water quality, and diatoms can be used to assess or track these alterations with effective biomonitoring. This requires consistent and reliable identification. The diatom flora in the present study is intended to serve as an image voucher of epilithic diatom taxa from the Mula-Mutha River Basin, a tropical river system located in the Western Ghats of India. These samples were collected seasonally from 19 stations during 2022 and 2023. 170 diatom taxa were documented and identified in this study. The morphological range of each taxon was imaged. Nitzschia (24), Navicula (20), and Gomphonema (17) commonly occurred across sites in the river basin. Approximately 4.11% (7 taxa) of the documented diatoms are potentially novel and have been provisionally numbered. There is a distinct and significant seasonal trend with seven taxa indicative of pre-monsoon conditions, eight taxa associated with monsoon flows, and a single post-monsoon indicator. To our knowledge, there are no previous studies that have comprehensively documented diatom diversity across the entire river basin. This study will serve as a reliable diatom identification resource and contribute towards improving taxonomic consistency and enabling comparisons for future monitoring efforts.